P171 A case of extensive oral and penile ulceration. (23rd May 2012) - Hartley, A; Paige, D; Buchanan, J; Hourihan, M; Adlington, R
Abstract : A 35-year-old Indian man was referred to the genitourinary clinic with a 3-month history of progressive, painful oral and penile ulceration. He had lost 10 kg in weight. He was anorexic secondary to mucosal pain but was otherwise well, with no reported rashes or eye problems. He had no significant medical history and took no regular medication. Last sexual intercourse was protected vaginal intercourse with a commercial sex worker 10 weeks earlier. On examination of the mouth, extensive ulceration was seen on the buccal mucosa and tongue; genital examination revealed superficial erosions on the glans penis and prepuce. Examination of the eyes, skin and joints was unremarkable. The differential diagnosis included: erosive lichen planus, aphthous ulcers, pemphigus vulgaris, cicatricial pemphigoid, Behçet's disease and secondary syphilis. Swabs from the oral ulcers were positive for Herpes simplex virus (HSV) type 1 DNA but penile swabs were negative for both HSV type 1 and 2. Hepatitis B, C, and syphilis serology, HIV antibody, and autoimmune profile were negative. Indirect immunofluorescence for epithelial intercellular cement was positive at a titre of 1:160. Biopsy of the oral lesions showed marked suprabasal acantholysis with prominent Tzank cell formation, in keeping with pemphigus vulgaris (PV). The patient was maintained on oral prednisolone with gradual improvement. Azathioprine will be used as a long-term steroid sparing agent. PV is a potentially fatal autoimmune blistering disorder of the skin and mucous membranes, more common in Indians. Cutaneous lesions are often absent. HSV can both mimic immunobullous disorders and cause superinfection. Therefore, positive HSV swabs must be taken in context and interpreted carefully. Patients may present to the GUM clinic with a history of mucosal ulceration and PV should be included in the differential of such cases.